2014
DOI: 10.1002/smi.2564
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Work Stress Assessment of Patients following Angioplasty or Heart Surgery: Results of 1‐year Follow‐up Study

Abstract: The aim of this study was to explore changes in subjective psychological health and perceived work stress among patients who returned to work (RTW) after a multidisciplinary cardiac rehabilitation (CR) following cardiac interventions. A total of 108 patients were evaluated at the beginning of their CR, at 6 and 12 months after discharge. Self-report questionnaires were used to assess depression, anxiety, illness perception and work stress at each time stage. Results showed reports of depressive symptoms signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 43 publications
0
17
0
1
Order By: Relevance
“…Specifically, the results showed that the best predictors of a satisfying RTW after cardiac invasive procedures were: job satisfaction for the pre-illness work environment, depression and ambition, independently of sociodemographic factors, medical factors and a type of RTW (full or partial). The key role in the RTW process after an acute cardiac event played by non-medical factors has been also explored by earlier research [3][4][5]9,[15][16][17][18][19][20][21][22][23]. Recent studies have shown that the perception of work environment, which can be reflected in work stress and job satisfaction, has a strong effect on both people's decision to RTW [16,21,22] and duration of sickness absence [15,16].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, the results showed that the best predictors of a satisfying RTW after cardiac invasive procedures were: job satisfaction for the pre-illness work environment, depression and ambition, independently of sociodemographic factors, medical factors and a type of RTW (full or partial). The key role in the RTW process after an acute cardiac event played by non-medical factors has been also explored by earlier research [3][4][5]9,[15][16][17][18][19][20][21][22][23]. Recent studies have shown that the perception of work environment, which can be reflected in work stress and job satisfaction, has a strong effect on both people's decision to RTW [16,21,22] and duration of sickness absence [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies have found that predictors of HRQL after a heart surgery or coronary angioplasty were primarily psychological and not related to the illness severity [13][14][15][16]. Instead, research on professional life and work reintegration after cardiac interventions have focused mainly on the identification of factors predicting RTW (i.e., working/not working) or time for RTW [3,4,[17][18][19], while very few studies have investigated the quality of work resumption, in terms of a patient's job satisfaction and re-adaptation to work [15][16][17][18][19][20][21][22]. Recent studies suggested an important role of psychosocial work environment in the RTW process, with particular emphasis on work stress and job satisfaction [15,16,18,19,21,22].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…RTW after a cardiac event is a multidimensional process which seems to be strongly influenced by psychosocial factors (2,9,(14)(15)(16)(17)(18)(19)(20)(21)(22). These psychosocial variables can both impede or facilitate RTW, and their identification is necessary in promoting and improving RTW among sick-listed cardiac patients (5,12,23,24). The goal of this article is to review the role of psychosocial factors in the RTW process after long-term sick leave due to a cardiac event.…”
Section: Introductionmentioning
confidence: 99%